2022
DOI: 10.1002/hsr2.789
|View full text |Cite
|
Sign up to set email alerts
|

Comparative risk assessment of COVID‐19 associated mucormycosis and aspergillosis: A systematic review

Abstract: COVID‐19 is not only limited to a defined array but also has expanded with several secondary infections. Two uncommon opportunistic fungal infections, COVID‐19 associated mucormycosis (CAM) and aspergillosis (CAA), have recently been highly acquainted by many worldwide cases. Two immune response deteriorating factors are considered to be responsible for immunosuppression: comorbidities and medication. Due to unlike infection sites and patterns, CAM and CAA‐associated factors deflect a few degrees of proximity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 156 publications
0
3
0
Order By: Relevance
“…Patients in our cohort may have been predisposed to developing CAM by preexisting diabetes mellitus or prediabetic state, steroid therapy, and compromised immune functions due to COVID-19, as observed in other studies. 7,9,15 Corticosteroid use is particularly implicated in the aetiopathogenesis of CAM, as a systemic immune response to invasive fungal infections, such as mucormycosis and aspergillosis, are found in a very high proportion of patients. 14 Steroid therapy may exacerbate gross alterations in lymphocyte and macrophage functions in COVID-19, and make patients particularly vulnerable to these kinds of invasive fungal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Patients in our cohort may have been predisposed to developing CAM by preexisting diabetes mellitus or prediabetic state, steroid therapy, and compromised immune functions due to COVID-19, as observed in other studies. 7,9,15 Corticosteroid use is particularly implicated in the aetiopathogenesis of CAM, as a systemic immune response to invasive fungal infections, such as mucormycosis and aspergillosis, are found in a very high proportion of patients. 14 Steroid therapy may exacerbate gross alterations in lymphocyte and macrophage functions in COVID-19, and make patients particularly vulnerable to these kinds of invasive fungal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Mucormycosis, also known as zygomycosis, is a fungal infection caused by ubiquitous organisms from the class of Zygomycetes, the order of Mucorales, most commonly by the genus Rhizopus [1]. The epidemiology, pathogenesis, clinical presentation, diagnosis, and management of mucormycosis have all been reviewed extensively, both independently [1,2] and in the context of COVID-19 [3][4][5][6][7]. These fungi are typical environmental organisms but can cause a devastating opportunistic infection, especially for immunosuppressed patients.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, very few CAM cases were reported outside India [9] . In Europe, fungal infections associated with COVID-19 were mainly COVID-19-associated pulmonary aspergillosis (CAPA), whereas CAM was rarer [10] . A multicentric prospective study in France [11] reported 76 proven/probable CAPA cases and 6 proven/probable CAM cases among 509 COVID-19 patients on mechanical ventilation.…”
Section: Introductionmentioning
confidence: 99%
“…A multicentric prospective study in France [11] reported 76 proven/probable CAPA cases and 6 proven/probable CAM cases among 509 COVID-19 patients on mechanical ventilation. Conversely, in India, few CAPA cases were reported compared with the CAM cases [10] .…”
Section: Introductionmentioning
confidence: 99%